Bahan Ajar Digital Kerjaan Kuningan dengan Model Inquiry untuk Meningkatkan Literasi Sejarah Siswa - Nur Amalia; Sariyatun Sariyatun; Leo Agung Sutimin (CV. Syntax Corporation Indonesia, 2021)
History in the twenty-first century, which must be oriented towards digital teaching materials. Historical learning can be drawn from some of the experiences that teachers do in the classroom. This research aims to explain the teaching materials used, explain the procedures for the development of digital teaching materials, test the effectiveness of the development of digital teaching materials. This development research procedure uses Research and Development (RND) with addie development model, data collection is done using questionnaires, observations, interviews and tests. The results of this study showed that the learning model used in Sma Negeri 3 Kuningan is still conventional and only uses one textbook, then the use of power points is less than optimal. The use of ADDIE design development products consists of five stages. The first analysis was conducted to analyze the need for digital teaching materials to improve the historical literacy of students at Sma Negeri 3 Kuningan. Both designs or product design stages consisting of the history of the Kingdom of Kuningan, the kings - kings who first occupied kuningan territory, and the teachings of madrais religion in the Cigugur area of Kuningan regency, syllabus adjustment, achievement of indicators, and RPP. The third development or product development stage is the process of validating product trial experts and conducting trials. And the fourth, implementation or implementation stage is the implementation of the final product or final product; and five evaluation or evaluation stages of effectiveness tests in experimental classes and control classes. The effectiveness of the Kuningan Kingdom teaching materials showed that the results of the historical literacy test with a signification value of 0.001<0.05. The results show that there is a significant influence on the use of digital teaching materials of the Kingdom of Kuningan during the Dutch East Indies through the inquiry model to improve historical literacy.